Methodology for selecting installation sites for automatic power redundancy systems of DC traction substations - A. L. Kashtanov; Yu. V. Plotnikov (Омский научный вестник, 2021)
The paper presents a method for selecting the installation locations of power reservation systems of traction substations to reduce electricity losses in the system of traction power supply of DC railways. The analysis of the main criteria affecting the efficiency and reliability of the DC traction power supply system is carried out. The algorithm for selecting the installation locations of power reservation systems has been developed, which allows selecting traction substations that provide the greatest energy effect during the installation of systems.